Making data talk : communicating public health data to the public, policy makers and the press - Nelson, David E., M.D.; Hesse, Bradford W.; Croyle, Robert T. (New York ; Oxford : Oxford University Press, 2009)
The authors summarize and synthesize research on the selection and presentation of data pertinent to public health and provide practical suggestions, based on this research summary and synthesis, on how scientists and other public health practitioners can better communicate data to the public, policy makers and the press.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Communication in public health; Health education